Marionettes Eight Little Pianoforte Pieces, Opus 38 - MACDOWELL, Edward (The Arthur P. Schmidt Co., 1901)
Lagu ini terdiri dari: Prologue, Soubrette, Lover, Witch, Clown, Villain, Sweetheart, Epilogue.